Do We Need Different Protocols To Support Group-Oriented Cryptosystem? - Gumel, L. A.; Leow, Soo Kar; Ramani, A. K. (Malaysian Journal of Computer Science, 1999)
Introduces some of the commonly known methods (protocols) used in key sharing/distribution problems, and finally shows that the existing protocols can be extended to support Group-Oriented Cryptoscheme (GOC). It is both a tutorial and an introduction to GOC.